Association of overall survival in patients with newly diagnosed glioblastoma with contrast-enhanced perfusion MRI: comparison of intraindividually matched T1- and T2*-based bolus techniques - Bonekamp, David; Deike-Hofmann, Katerina; Wiestler, Benedikt; Wick, Wolfgang; Bendszus, Martin; Radbruch, Alexander; Heiland, Sabine (Journal of magnetic resonance imaging, 2015)
Background To compare intraindividual dynamic susceptibility contrast (DSC) and dynamic contrast enhanced (DCE) MR perfusion parameters and determine the association of DCE parameters with overall survival (OS) with the established predictive DSC parameter cerebral blood volume (CBV) in patients with newly diagnosed glioblastoma. Methods Perfusion data were analyzed retrospectively, and included scans performed preoperatively at 3.0 Tesla in 37 patients (25 males, 12 females, 39-83 years, median 65) later diagnosed with glioblastoma. All patients received standard treatment consisting of surgery and radiochemotherapy. Images were spatially coregistered and maximum region of interest-based DCE and DSC parameter measurements compared and thresholds identified using multivariate linear regression, Pearson's correlation coefficients and using receiver operating characteristic analysis. Survival analysis was performed using Kaplan-Meier curves. Results While both, elevated volume transfer constant (Ktrans) (>0.29 min−1; P = 0.041) and CBV (>23.7 mL/100 mL; P < 0.001) were significantly associated with OS, elevated CBV was associated with worse OS compared with elevated Ktrans. Ktrans was significantly correlated with the leakage correction factor K2 but not with CBV. Conclusion The combined use of DSC and DCE MR perfusion may provide additional information of prognostic value for glioblastoma patient survival prediction. As Ktrans was not tightly coupled to CBV, both parameters may reflect different stages in the pathogenetic sequence of glioblastoma growth. J. Magn. Reson. Imaging 2015;42:87-96. © 2014 Wiley Periodicals, Inc.